The Socio-demographic Dimension of the Informal Labour Force in Urban Nepal - Adhikari, Dipak Bahadur; Nepal, Pramshu (Journal of Development and Administrative Studies, 2023)
The objective of this study is to analyze the socio-demographic characteristics of the labour force, and features of the urban informal economy, with a focus on Nepal. Specifically, it seeks to pinpoint the primary economic endeavors and the ways in which they serve as a constructive financial engine and employment generation for household livelihood. In order to achieve this, the researcher conducted a primary survey through a structured questionnaire. Descriptive statistics, chi-square, percentages, and different forms of graphs were used in the investigation. The analysis of the sampled respondents revealed that informal work is a dominant occupation, with about two-thirds of household heads engaged in this sector. Among the respondents, job in the informal sector was the first-hand job for about 75 percent. Over one-third of the respondents have worked for five years or less in a particular informal business and service sector. The findings show that many people have been involved in the informal sector after Nepal's great earthquake of 2015. About two-thirds of the respondents are migrants, whereas 62 percent migrated from their own country and 9 percent emigrated from India.